Amphiphilic γ-cyclodextrin–fullerene complexes with photodynamic activity. Issue 1 (2nd November 2021) - Miki, Koji; Dan Zhang, Zi; Kaneko, Kaho; Kakiuchi, Yui; Kojima, Kentaro; Enomoto, Akane; Oe, Masahiro; Nogita, Kohei; Murata, Yasujiro; Harada, Hiroshi; Ohe, Kouichi
Abstract : High-speed vibration milling of a mixture of lipophilic γ-cyclodextrin (γ-CD), hydrophilic γ-CD and fullerene or functionalization of preformed γ-CD–fullerene complexes afforded amphiphilic γ-CD–fullerene complexes with high photodynamic activity. Abstract : Amphiphilic γ-cyclodextrin–fullerene 2 : 1 complexes (CL FCH complexes) were prepared by high-speed vibration milling of lipophilic tail-grafted γ-cyclodextrin (γ-CD), hydrophilic tail-grafted γ-CD and fullerene C60 . The transamidation of γ-CD–fullerene complexes having two amino groups with lipophilic and hydrophilic activated esters also afforded amphiphilic CL FCH complexes. Self-assemblies consisting of amphiphilic CL FCH complexes efficiently generated singlet oxygen under photoirradiation. Under visible light irradiation conditions, CL FCH complexes bearing a vitamin E moiety as a lipophilic tail showed high photodynamic activity toward cancer cells.